Da paisagem aos ritos: processo de formação dos sambaquis da ilha de São Luís, Maranhão - MORAES, Lucio Adriano Teixeira de (2024)
The shell mounds of São Luís Island, in Maranhão, are the focus of this study, aiming to understand their origin, function, chronology, and cultural significance, as well as to contextualize them in the coastal archaeological landscape and establish connections with local prehistoric populations. Employing a multidisciplinary approach combining literature review, zooarchaeology studies, and landscape archaeology, the research unveils the historical and cultural complexity of these sites. New discoveries, such as the nutritional importance of fish compared to mollusks, have altered the understanding of the subsistence strategies of these societies over time. Additionally, the importance of preserving these sites in the face of contemporary threats, such as urbanization and environmental degradation, is emphasized, highlighting the need for effective conservation and valorization policies for Maranhão's archaeological and cultural heritage. The integration of new data from ongoing research aims to deepen the analysis of these sites, contributing to a more comprehensive and updated understanding of the history and culture of this region of significant archaeological importance.